Administrative stressors and psychological and physiological symptoms among novice primary school principals - Yii Chai Ling; Lokman Mohd Tahir; Mohd Fadzli Ali; Roslee Ahmad; Siti Nisrin Mohd Anis; Roslizam Hassan (International Journal of Evaluation and Research in Education (IJERE), 2022)
This study was conducted to identify whether the administrative workloads led to the stress level among novice principals in their new schools. In addition, we also explore whether the principals are experiencing the psychological and psychological symptoms from their stress issue. The data collection consisted of two major phases. In the first phase, questionnaires were administered to 70 novice primary principals who were just being appointed at their new schools. It was followed by three sessions of interviews with purposely selected 10 novice primary principals as the second phase. From the quantitative data analysis, primary principals perceived their schools’ administrative stress caused them a moderate stress level from their heavy administrative workloads. However, principals reported having psychological and physiological symptoms from the quantitative findings and interview sessions.